PENGENDALIAN KUALITAS PRODUK ELPIJI PSO (Public Service Obligation) DENGAN IMPLEMENTASI STATISTICAL PROCESS CONTROL - Arif, Donny; Yucha, Nikma (Universitas Nahdlatul Ulama Surabaya, 2021)
Domestic Gas Region V is division of the company PT Pertamina Persero which is engaged in providing domestic LPG, especially in the field distribution of PSO and non PSO LPG. Domestic Gas supply LPG through SPPBE (Station for Filling and Transporting LPG Bulk) to agents to direct consumers. Especially for the PSO LPG with a weight 3kg is product of government subsidies with large scale production, it is necessary equalization of good quality for use by the middle to lower class society. In ptactices, many consumers feel that there are several differences between products one another, especially the difference in the weight of the filled tube and the diameter of the valve that is not the same, so ut is difficult to install with the stove regulator and can cause gas leakage which in turn caused a fire. Implementation of statistical process control is carried out to measure the quality of LPG PSO so that it is expected to be able to maintain and improve the quality of PSO LPG products. Statistical process control is done because it exists differences in quality dispersion with the same product this needs to be done to meet the wants and needs of consumers and increase customer satisfaction. This research was conducted to measure the effectiveness/success in controlling and supervision of product quality by implementing statistical process control, the first is to measure the description of the quality of LPG products, the second is to measure how consumer satisfaction with LPG products. The results obtained show that statistical process control analysis illustrates that the performance criteria set by the holding company of PT Pertamina has been very good seen from the P-Chart control which produces the value “P” is in the lower limit of the lower control limit.